2004
DOI: 10.1021/cm049648r
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Measurements in Molecular Electronics

Abstract: This paper reviews the various methods used to measure the electrical characteristics of individual or small groups of molecules, including crossed-wire junctions, mechanically controllable break junctions, conducting atomic force microscopy, scanning tunneling microscopy, molecular electronics on silicon surfaces, the NanoCell, nanopores, and other devices. It is shown that in the most common embodiment, the metal-molecule-metal junction, the assembly must be considered in whole. The characteristics of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
151
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 72 publications
0
151
0
1
Order By: Relevance
“…7,8 Terminal anchor groups which have an affinity for gold are attached to the molecules to achieve the in situ assembly of metal-molecule-metal junctions. 9,10,11 The electrical conductance of these nanoscale junctions is characterized using a range of techniques, notably, scanning tunneling microscopy (STM) 12,13 conductive-probe atomic force microscopy (CP-AFM), 14,15 scanning tunneling microscopy break junctions (STM-BJs) 16,17,18 and mechanically controlled break junctions (MCBJs). 19,20,21 Studies which aim to understand how charge transport mechanisms vary with changing the length of the molecular wire 22,23 have been very limited due to the challenges posed by the synthesis, rigorous purification and measurement of long molecules anchored between two electrodes.…”
Section: Molecular Electronicsmentioning
confidence: 99%
“…7,8 Terminal anchor groups which have an affinity for gold are attached to the molecules to achieve the in situ assembly of metal-molecule-metal junctions. 9,10,11 The electrical conductance of these nanoscale junctions is characterized using a range of techniques, notably, scanning tunneling microscopy (STM) 12,13 conductive-probe atomic force microscopy (CP-AFM), 14,15 scanning tunneling microscopy break junctions (STM-BJs) 16,17,18 and mechanically controlled break junctions (MCBJs). 19,20,21 Studies which aim to understand how charge transport mechanisms vary with changing the length of the molecular wire 22,23 have been very limited due to the challenges posed by the synthesis, rigorous purification and measurement of long molecules anchored between two electrodes.…”
Section: Molecular Electronicsmentioning
confidence: 99%
“…Representative results on the applications of nanogap electrodes in nano-and single molecular devices have been summarized by several authoritative reviews. [164][165][166][167][168][169][170][171][172][173] Limited by the capacity of the present paper, we do not plan to overlap these reviewed topics, and only focus on the possibility of combining conjugated polymers with nanogap electrodes, in order to introduce the properties associated with conjugated polymers into such nanodevices. Based on our recent experience, [156,[174][175][176][177] we will exemplify this combination using a Since the discovery of conductive polymers in the 1970s, thousands of conjugated polymers have been synthesized and investigated, and some have been successfully applied in polymer electronics since the 1990s.…”
Section: Applicationsmentioning
confidence: 99%
“…In the intervening years there has been a wealth of further experimental and computational studies of molecular junctions and many aspects of the problem have been revealed (see, for example, [4][5][6][7] and references therein) such as the importance of the contact regions between molecule and electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Metzger [3] presented further experimental results, where the DσA molecular junction was formed from a Langmuir-Blodgett multi-or monolayer with a second electrode deposited onto the L-B layer. The molecule was γ-(n-hexadecyl)quinolinum tricyanoquinodimethanide Substantial rectifying behaviour for the molecular junction was evident in the results with an asymmetry in the i(V) curve of several orders of magnitude between forward and reverse bias.In the intervening years there has been a wealth of further experimental and computational studies of molecular junctions and many aspects of the problem have been revealed (see, for example, [4][5][6][7] and references therein) such as the importance of the contact regions between molecule and electrode. …”
mentioning
confidence: 99%